A new species of crown-of-thorns sea star, Acanthaster benziei sp. nov. (Valvatida: Acanthasteridae), from the Red Sea - Wörheide, Gert; Kaltenbacher, Emilie; Cowan, Zara-Louise; Haszprunar, Gerhard (Zootaxa, 2022)
A new species of crown-of-thorns sea star (CoTS), Acanthaster benziei sp. nov., is described based on four specimens collected from Saudi Arabia’s Red Sea coast where it inhabits coral reefs. Species delimitation from congeners in the species complex, i.e., Acanthaster planci, Acanthaster mauritiensis and Acanthaster cf. solaris, is primarily based on distinct and diagnostic mitochondrial DNA sequence regions. Species separation of Acanthaster benziei is additionally justified due to diagnostic morphological characters: fewer arms; narrower and thinner spines; fanned spine tips in primary and latero-oral spines; a wider tip or tapering shape in circumoral spines; and rhombus-shaped oral pedicellariae.